Pembuatan Kopi Excelsa (Coffea liberica var. Dewerei.) Wine dengan Variasi Tingkat Roasting dan Lama Fermentasi - Fadhila, Irvandy N; Bimantio, Mohammad P; Arialistya, Yhone (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Wine coffee is produced through an extended fermentation process, during which the intensity of its flavor and aroma increases. The coffee variety used in this study is excelsa, known for its naturally sour profile and strong aroma, characterized by a unique combination of sour, sweet, and astringent flavors. The objectives of this study were to determine the effects of fermentation duration and roasting level on the alcohol content of excelsa wine coffee and to determine its sensory attributes. The study employed a Randomized Complete Block Design with two factors: fermentation duration (factor X) and roasting level (factor Y). The parameters analyzed included moisture content, ash content, caffeine content, alcohol content, and organoleptic test, which includes preference for color, aroma, and taste of the excelsa wine coffee brew. From the results of this study, it was found that the water content, ash content, caffeine content, alcohol content, and sensory evaluation (color, aroma, and taste preference) of the excelsa wine coffee brew. The results showed that moisture, ash, and caffeine contents met the specified quality standards. The best sensory results were obtained from samples fermented for 30 days and roasted at a medium level, producing a well-balanced taste, neither overly sour nor predominantly bitter.